2016
DOI: 10.1002/2016jd025317
|View full text |Cite
|
Sign up to set email alerts
|

Deep convection in elliptical and polygonal eyewalls of tropical cyclones

Abstract: In observations, tropical cyclones with cyclonically rotating elliptical eyewalls are often characterized by wave number 2 (WN2) deep convection located at the edge of the major axis. A simple modeling framework is used to understand this phenomenon, where a nondivergent barotropic model (NBM) is employed to represent the elliptical vortex in the free atmosphere, and an asymmetric slab boundary layer (SBL) model is used to simulate the frictional boundary layer (BL) underneath the free atmosphere. The interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 32 publications
(77 reference statements)
1
11
0
Order By: Relevance
“…e periodic cycles in the eyewall convection were also reproduced satisfactorily in the simulation during model hours 31-38. We analyzed the stage with a relatively steady IR (model hours [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] to determine the effects of the short-term periodic activities of eyewall convection on TC intensification. e simulation showed that convection of the eyewall of Hato exhibited periodic cycles with a period of 3-5 h, which limited the RI of Hato.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…e periodic cycles in the eyewall convection were also reproduced satisfactorily in the simulation during model hours 31-38. We analyzed the stage with a relatively steady IR (model hours [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] to determine the effects of the short-term periodic activities of eyewall convection on TC intensification. e simulation showed that convection of the eyewall of Hato exhibited periodic cycles with a period of 3-5 h, which limited the RI of Hato.…”
Section: Discussionmentioning
confidence: 99%
“…A similar analysis of Hurricane Olivia (1994) showed an elliptical TC vortex rotating with wavenumber-1 deep convection in the presence of strong vertical wind shear [33]. Kuo et al [34] demonstrated that the boundary layer (BL) radial inflow is also in control of the deep convection period. From radar observations of Typhoon Guillermo (1997), Reasor et al [27] identified convective burst cycles with a period of 0.6-2 h. Cycles began with the convective burst appearing in the downshear-left quadrant and ended with the cyclonic wrapping of upper-level updrafts into the downshear side of the eyewall.…”
Section: Introductionmentioning
confidence: 99%
“…Due to sampling limitations of the radar beam, it is unclear whether this coupling originates in the boundary layer or is only in the free troposphere. Kuo et al (2016) used a nondivergent barotropic model for the free atmosphere and an asymmetric slab boundary layer underneath and found a tangential wind maximum at the minor axis of the elliptic vortex in the free atmosphere, whereas the wind maximum was closer to the major axis within the boundary layer. In a real, baroclinic vortex that decays with height, the theoretical wave speed for VRWs is height dependent such that a vertically coherent asymmetry that propagates at the same speed over some depth will deviate from the theory at different levels.…”
Section: 1029/2020gl087919mentioning
confidence: 99%
“…Polygonal eyewalls are hypothesized to be the result of asymmetric vorticity dynamics that can modulate TC structure and intensity through counter‐propagating vortex Rossby waves (VRWs) (Hendricks et al., 2012; Kuo et al., 1999, 2016; Muramatsu, 1986; Schubert et al., 1999). A sign reversal of the mean radial vorticity gradient that acts as a waveguide for VRWs satisfies the Rayleigh condition for barotropic‐baroclinic instability (Montgomery & Shapiro, 1995), which can lead to a breakdown of the potential vorticity (PV) ring and redistribution of eyewall PV and angular momentum (Bell & Montgomery, 2008; Schubert et al., 1999) that can accelerate the mean wind inside the radius of maximum wind (RMW), and promote the contraction of the RMW.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation